Various Dimensions of Globalization and Their Implications for The Leadership and Management of Education - Rifai, Irfan (Bina Nusantara University, 2013)
Globalization impacts worldwide societies in economic, social, political, cultural and many other aspects. Helped by the great invasion of technology, these impacts are accelarated in the past few years. Countries of the world are now competing, strengthening alliances, and restructuring themselves: in and out, to be able to cope with the fast changing world. This is a salient moment for educational sector. Realizing how vital its role is, governments are advised not to take wrong implications considering its damaging impacts. This article presents the various dimensions of globalizations taken from different resources and offers implications that leaders of educational sector can do to cope with the challenges of the globalized world have to offer.